The Impact of Green Corporate Social Responsibility on Employee Green Well-being and Creativity - Bettayeb, Hafidha; Al-Hawari, Mohammad (International Review of Management and Marketing, 2024)
This paper assesses the impact of green Corporate Social Responsibility (CSR) on employee green well-being and creativity among hospitality enterprises in the United Arab Emirates (UAE). It considers the moderating impact of employee green value on the relationship between employee green well-being and creativity. The study employed a quantitative research design, utilizing 213 responses from employees working in hospitality firms in various cities across the UAE. It used the statistical software Smart PLS, which revealed two key findings. First, employees reported higher levels of well-being when their companies placed a greater emphasis on green CSR. Second, the study findings showed a positive relationship between employee green well-being and creativity. However, the discussion found no strong evidence supporting the importance of employee green value as a moderator. These findings have significant implications for the hospitality industry, as they propose that incorporating green CSR projects into strategic planning and development processes can improve employee green well-being and creativity, which will ultimately enhance the company’s performance.